Le siècle du jazz : art, cinéma, musique et photographie de Picasso à Basquiat - Baudoin, Philippe; Bianchi, Filippo; Capua, Enzo; Carles, Philippe; Cooper, Harry; Criqui, Jean-Pierre; Damisch, Hubert; De Smet, Catherine; Fayenz, Franco; Gabbard, Krin; Hofstein, Francis; Mouëllic, Gilles; et al. (Paris : Skira Flammarion ; Paris : Musée du quai Branly, 2009)
Adami, Valerio ; Albers, Josef ; Alechinsky, Pierre ; Altan, Francesco Tullio ; Avedon, Richard ; Barbelle, Albert ; Basquiat, Jean-Michel ; Bearden, Romare ; Benton, Thomas Hart ; Bibbs, Hart Leroy ; Brötzmann, Peter ; Brown, Frederick J. ; Buffet, Bernard ; Cieslewicz, Roman ; Clark, Claude ; Claxton, William ; Cocteau, Jean ; Colescott, Robert ; Colin, Paul ; Combas, Robert ; Covarrubias, Miguel ; Crepax, Guido ; Dali, Salvador ; Davie, Alan ; Davis, Stuart ; DeCarava, Roy ; de Forest, Lee ; De Kooning, Elaine ; Delaney, Joseph ; Delaunay, Charles ; Delavier, Maurice ; de Staël, Nicolas ; Suvero, Mark di ; Douglas, Aaron ; Dove, Arthur Garfield ; Dubuffet, Jean ; Eames, Charles & Ray ; Ernst, Jimmy ; Fleischer, Dave ; Flora, Jim ; Freed, Leonard ; Freleng, Isadore 'Friz' ; Frew, John ; Friedlander, Lee ; Fromanger, Gérard ; Garrigue, Alain ; Gnoli, Domenico ; Goldblatt, Burt ; Goursat, Georges ; Grosz, George ; Guttuso, Renato ; Gyarmathy, Michel ; Hammons, David ; Haring, Keith ; Hayden, Palmer ; Hirschfeld, Albert ; Humair, Daniel ; Iribe, Paul ; Israel, Marvin ; Janco, Marcel ; Jefferson, Louise E. ; Joans, Ted ; Johnson, William H. ; Joos, Louis ; Kane, Art ; Klarwein, Mati ; Kupka, Frantisek ; Lawrence, Jacob ; Le Corbusier ; Querrec, Guy Le ; Leff, Sidney ; Leger, Fernand ; Leonard, Herman ; Lichtenstein, Roy ; Loos, Adolf ; de Loustal, Jacques ; Lubalin, Herb ; Makowski, Tadeusz ; Marclay, Christian ; Marsh, Reginald ; Masotti, Roberto ; Matisse, Henri ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Matulka, Jan ; McLaren, Norman ; Merlin, Pierre ; Mili, Gion ; Miles, Reid ; Mondriaan, Piet ; Monory, Jacques ; Motley, Archibald Jr. ; Murphy, Dudley ; Murphy, Gérald ; Nauman, Bruce ; Noël, Georges ; Novelli, Gastone ; Oehlen, Albert ; etc.
Catalogue de l'exposition présentée au museo di arte moderna e contemporanea di Trento e Rovereto, 15.11.2008-15.02.2009, au musée du quai Branly, Paris, 15.03.2009-28.06.2009, au centre de cultura contemporania de Barcelona, 21.07.2009-18.10.2009
boek
Keywords: History of Jazz - Art - Cinema - Music - Photography - 20th century